Forewarned is forearmed: the hidden curriculum of working with police crime data - Curtis-Ham, Sophie (The crime data handbook, 2024)
Police administrative data systems are an increasingly accessible and varied source of crime data. This chapter outlines the many human and technological intricacies of working with police crime data as a researcher - which are often learned as tricks of the trade over many years. To reveal this ‘hidden curriculum’, we draw from our experiences of working with and within police organizations in England and New Zealand researching crime and policing. We describe the potential for police data to be used in crime research, highlighting opportunities presented by previously underutilized sources. We then cover the pitfalls that researchers new to this area should be forewarned about when acquiring, cleaning, analysing and interpreting police crime data. These arise from the design of data-recording systems, (lack of) data completeness and accuracy, and the many pains - technical and bureaucratic - involved in accessing and understanding different data sources. Throughout we weave advice to circumvent the trials and tribulations that come with obtaining and using police crime data in research.